The Impact of Coal Power Plant Emissions on Indonesia's Carbon Tax Rates - Arif Rahman Hakim; Vita Sarasi; Eddy Prahasta (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan)
Indonesia, as one of the top ten global carbon emitters, largely due to its heavy reliance on coal-fired power plants, has introduced a carbon tax policy to address the environmental impacts and mitigate carbon emissions. This study investigates the dynamic effects of coal power plant emissions on Indonesia's carbon tax rates by applying a system thinking approach utilizing a Causal Loop Diagram (CLD). The CLD is used to map the complex interactions between carbon emissions, economic factors, and regulatory policies, focusing on Indonesia’s carbon tax policy framework from its inception in 2021 through its early implementation stage in 2022, with projections extending to 2025. The CLD analysis identifies three key feedback loops : a reinforcing loop where economic growth and electricity demand increase coal consumption and CO2 emissions, a balancing loop where carbon tax revenues stimulate renewable energy investments to reduce fossil fuel dependency, and a policy feedback loop that strengthens fiscal capacity for climate mitigation efforts. Scenario analysis suggests that increasing the carbon tax rate from IDR 30/kg CO2e to IDR 150/kg CO2e could significantly reduce emissions while maintaining economic stability, particularly in the energy sector, if accompanied by targeted subsidies and incentives for renewable energy. The findings contribute new policy insights on how carbon taxes can be optimized to achieve environmental conservation goals while minimizing negative economic impacts and promoting a sustainable energy transition in Indonesia.